Stress Interferences between Fractures and Fracturing Stages of a Horizontal Well in a Sandy Conglomerate Reservoir in Junggar Basin, Northwest China. (17th April 2023) - Li, Jianmin; Du, Binghui; Ma, Junxiu; Liu, Ruining; Shi, Can; Lin, Botao
Abstract : The sandy conglomerate reservoirs in the Mahu oilfield located in the Junggar Basin of Northwest China are featured by a significant horizontal stress difference between two directions, making formations easy to form double-wing fractures upon hydraulic fracturing instead of creating a complex fracture network. In addition, as the well spacing or interval cluster spacing decreases, the stress interferences between hydraulic fractures strengthen accordingly, leading to more difficulties in the prediction of fracture propagation patterns. Given the geological characteristics in the study area, an extended finite element method (XFEM) based hydraulic fracture model that can handle fracturing fluid flow distribution was proposed to evaluate the seepage, stress, and damage of the formation under hydraulic fracturing. The influences of the initial stress difference, cluster spacing, and fracturing stage sequence on the hydraulic fracture stress interference and the fracture propagation were investigated, producing discoveries that include: (1) as the fractures propagate, the stress difference between two fractures changes as well, and such change is also affected by the initial stress difference and the fracture distance; (2) the postfracturing stress difference first decreases but then increases with the increase in cluster spacing; (3) as the cluster spacing increases, the interfracture stress interference decreases. In addition, the outer fractures suppress the length of the middle fractures, thus limiting the stimulated reservoir area (SRA); (4) for the cases of creating multistage fractures, the later fracturing stage experiences both the interfracture and the interstage stress interferences from the prefracturing stage. As the fracture width changes with time, the nonplanar fracture feature of the later fracturing stage becomes more evident while the corresponding SRA decreases.